Fabrication and properties of waterborne thermoplastic polyurethane nanocomposite enhanced by the POSS with low dielectric constants. (17th November 2020) - Zhao, Hui; Zhao, Si-Qi; Li, Qing; Khan, Muhammad Rafiullah; Liu, Yang; Lu, Peng; Huang, Chong-Xing; Huang, Li-Jie; Jiang, Tao
Abstract: Polyhedral oligomeric silsesquioxane (POSS) functionalized with an amine group was designed and prepared. Then it was applied as a physical cross-linker to prepare waterborne thermoplastic polyurethane (WTPU)/POSS nanocomposite. Results revealed that the POSS had a little influence on the viscosity and storage stability of the WTPU/POSS dispersions. Moreover, the cured nanocomposite film with 8 wt% POSS showed superior surface hydrophobicity, the water contact angle was higher than 121° due to the migration of POSS on the surface, while the tensile strength increased up to 6.7 MPa and the elongation at break was higher than 800%. Dynamic thermomechanical analysis (DMA) results revealed a significant increase in the glass transition temperature (Tg) of the nanocomposite, the dielectric constant decreased from about 2.60 to 1.83. This POSS can made the polymer with excellent physical properties and low dielectric constant, which could be applied in integrated circuitry micro devices. Graphical abstract: Image 1 Highlights: Functionalized POSS with a single amine group was synthesized. The WTPU containing functionalized POSS exhibited superior hydrophobicity and enhanced mechanical properties. The WTPU/POSS films were still thermoplastic and possessed reprocessing ability and reusability.